Changes in Blood microRNA Expression and Early Metabolic Responsiveness 21 Days Following Bariatric Surgery - Atkin, Stephen L.; Ramachandran, Vimal; Yousri, Noha A.; Benurwar, Manasi; Simper, Steven C.; McKinlay, Rodrick; Adams, Ted D.; Najafi-Shoushtari, S. Hani; Hunt, Steven C. (Frontiers in Endocrinology, 2019)
Background. Early metabolic responses following bariatric surgery appear greater than the initial weight loss and coincide with remission/improvement in diabetes. We hypothesized that small noncoding microRNA changes might contribute to regulating mechanisms for weight loss and diabetes remission. Methods. 29 type 2 diabetes patients (mean BMI 46.2 kg/m2) underwent Roux-en-Y gastric bypass (RYGB) surgery. Clinical measurements and fasting blood samples were taken preoperatively and at day 21 postoperatively. Diabetes remission following bariatric surgery was defined as withdrawal of anti-diabetic medication, fasting glucose <126 mg/dl (7 mmol/L) and HbA1c <6.5%. microRNA expression was determined by quantitative polymerase chain reaction. Results. BMI decreased by 3.8 kg/m2 21 days postoperatively. Eleven of 29 RYGB (38%) had diabetes remission. Changes from pre- to post-surgery in 32 of 175 microRNAs were nominally significant (p<0.05). Following multiple comparison adjustment, changes in seven microRNAs remained significant: miR-7-5p, let-7f-5p, miR-15b-5p, let-7i-5p, miR-320c, miR-205-5p, and miR-335-5p. Four pathways were over-represented by these seven microRNAs, including diabetes and insulin resistance pathways. Only one microRNA was nominally associated with diabetes remission 21 days post-surgery (p<0.05): miR-132-3p. Conclusion. Seven microRNAs showed significant changes 21 days after bariatric surgery. Functional pathways of the altered microRNAs were associated with diabetes-, pituitary- and liver-related disease, with expression in natural killer cells, and pivotal intestinal pathology suggesting possible mechanistic roles in early diabetes responses following bariatric surgery.